Pregnancy related hormones increase CYP3A mediated buprenorphine metabolism in human hepatocytes: a comparison to CYP3A substrates nifedipine and midazolam - Fashe, Muluneh M.; Miner, Taryn A.; Fallon, John K.; Schauer, Amanda P.; Sykes, Craig; Smith, Philip C.; Lee, Craig R. (Frontiers in Pharmacology, 2023)
Introduction: Pregnancy increases the clearance of CYP3A4 substrate drugs and pregnancy-related hormones (PRHs) induce hepatic CYP3A4 expression and metabolism. However, it remains unclear to what extent the magnitude of PRH-evoked changes in hepatic CYP3A metabolism varies across multiple substrates. This study quantified the impact of PRHs on CYP3A protein concentrations and buprenorphine metabolism in human hepatocytes, and compared the magnitude of these effects to nifedipine and midazolam metabolism. Methods: Sandwich-cultured human hepatocytes (SCHH) from female donors were exposed to PRHs, administered in combination across a range of physiologically relevant concentrations, for 72 h. Absolute protein concentrations of CYP3A4, CYP3A5, and CYP3A7 in SCHH membrane fractions were quantified by nanoLC-MS/MS, and norbuprenorphine (nor-BUP), dehydro-nifedipine (dehydro-NIF), and 1-hydroxy-midazolam (1-OH-MDZ) formation was evaluated. Results: Compared to control, PRH exposure increased CYP3A4, CYP3A7, and total CYP3A protein concentrations, but not CYP3A5 concentrations, and increased nor-BUP, dehydro-NIF, and 1-OH-MDZ formation in a concentration-dependent manner. The formation of nor-BUP, dehydro-NIF, and 1-OH-MDZ each positively correlated with PRH-mediated changes in total CYP3A protein concentrations. The PRH-evoked increase in nor-BUP formation was evident in all donors; however, the PRH induction of dehydro-NIF and 1-OH-MDZ formation was diminished in a hepatocyte donor with high basal CYP3A5 expression. Discussion: These findings demonstrate that PRHs increase buprenorphine, nifedipine, and midazolam metabolism in SCHH via induction of CYP3A4 and total CYP3A protein concentrations, and the magnitude of these effects vary across hepatocyte donors in a substrate-specific manner. These data provide insight into the contribution of PRH induction of CYP3A4 metabolism to increased buprenorphine clearance during pregnancy.